1997
DOI: 10.1161/01.str.28.9.1686
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Function Analysis of Cerebral Autoregulation Dynamics in Autonomic Failure Patients

Abstract: These data indicate an altered, yet present, autoregulatory response with autonomic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
192
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(206 citation statements)
references
References 33 publications
12
192
2
Order By: Relevance
“…The BP-BFV phase shifts were similar to those observed during the Valsalva maneuver obtained from the MMPF method [17]. Such positive phase shift has been also reported using Fourier transform methods during head-up tilt, and was interpreted as a faster recovery of BFV mediated by the compensatory cerebral autoregulatory mechanisms [8,12,14,50]. Our previous studies showed that the reduction of the MMPF derived BP-BFV phase shifts was associated with impaired cerebral autoregulation in stroke and hypertensive subjects and in patients with traumatic brain injuries [17,51], indicating that MMPF results reflect dynamics of cerebral autoregulation.…”
Section: A Assessment Of Nonlinear Interactions Between Nonstatisupporting
confidence: 79%
See 2 more Smart Citations
“…The BP-BFV phase shifts were similar to those observed during the Valsalva maneuver obtained from the MMPF method [17]. Such positive phase shift has been also reported using Fourier transform methods during head-up tilt, and was interpreted as a faster recovery of BFV mediated by the compensatory cerebral autoregulatory mechanisms [8,12,14,50]. Our previous studies showed that the reduction of the MMPF derived BP-BFV phase shifts was associated with impaired cerebral autoregulation in stroke and hypertensive subjects and in patients with traumatic brain injuries [17,51], indicating that MMPF results reflect dynamics of cerebral autoregulation.…”
Section: A Assessment Of Nonlinear Interactions Between Nonstatisupporting
confidence: 79%
“…A transfer function is typically used to explore the relationship between blood pressure (BP) and blood flow velocity (BFV) by calculating gain and phase shift between the BP and BFV power spectra [2,8,[10][11][12][13][14][15][16]. In this approach, it is presumed that signals are stationary, and are composed of superimposed sinusoidal oscillations of constant amplitude and period at a pre-determined frequency range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Diehl et al, a decrease of the phase angle below 60-90°i ndicates a more passive behavior of the cerebral vessel bed and is an indicator of impaired cerebral autoregulation [20,22,24]. In both our groups, the phase shift remained stable during LBNP confirming the assumptions of intact cerebral autoregulation during LBNP.…”
Section: Discussionsupporting
confidence: 76%
“…We normalized the transfer function gain by dividing the LF transfer function gain by the mean values of the input signal BP and the output signal CBFV of cerebral autoregulation, i.e. by cerebrovascular conductance (CBFV/BP) of each patient [24].…”
Section: Lbnp Protocolmentioning
confidence: 99%